Molecular cloning and characterization of an adenosine receptor: the A3 adenosine receptor. - Zhou, Q Y (1992)
We have previously reported the selective amplification of several rat striatal cDNA sequences that encode guanine nucleotide-binding regulatory protein (G protein)-coupled receptors. One of these sequences (R226) exhibited high sequence identity (58%) with the two previously cloned adenosine receptors. A full-length cDNA clone for R226 has been isolated from a rat brain cDNA library. The cDNA clone encodes a protein of 320 amino acids that can be organized into seven transmembrane stretches. R226 has been expressed in COS-7 and CHO cells and membranes from the transfected cells were screened with adenosine receptor radioligands. R226 could bind the nonselective adenosine agonist tritiated N-ethyladenosine 5'-uronic acid ([3H]NECA) and A1-selective agonist radioiodinated N6-2-(4-amino-3-iodophenyl)-ethyladenosine ([125I]APNEA) but not A1-selective antagonists tritiated 1,3-dipropyl-8-cyclopentylxanthine ([3H]DPCPX) and 8-(4-[([[(2-aminoethyl)amino]carbonyl]methyl)oxy]-phenyl)-1, 3-dipropylxanthine ([3H]XAC) or the A2-selective agonist ligands tritiated 2-[4-(2-carboxyethyl)phenyl]ethyl-amino 5'-N-ethylcarboxamidoadenosine ([3H]CGS21680) and radioiodinated 2-[4-([2-[(4-aminophenyl)methylcarbonylamino] ethylaminocarbonyl]ethyl)phenyl]ethylamino 5'-N-ethylcarboxamidoadenosine. Extensive characterization with [125I]APNEA showed that R226 binds [125I]APNEA with high affinity (Kd = 15.5 +/- 2.4 nM) and the specific [125I]APNEA binding could be inhibited by adenosine ligands with a potency order of (R)-N6-phenyl-2-propyladenosine (R-PIA) = NECA greater than S-PIA greater than adenosine greater than ATP = ADP but not by antagonists XAC, isobutylmethylxanthine, and DPCPX. In R226 stably transfected CHO cells, adenosine agonists R-PIA, NECA, and CGS21680 inhibited by 40-50% the forskolin-stimulated cAMP accumulation through a pertussis toxin-sensitive G protein with an EC50 of 18 +/- 5.6 nM, 23 +/- 3.5 nM, and 144 +/- 34 nM, respectively. Based on these observations we conclude that R226 encodes an adenosine receptor with non-A1 and non-A2 specificity, and we thus name it the A3 adenosine receptor. mRNA analyses revealed that the highest expression of R226 was in the testis and low-level mRNAs were also found in the lung, kidneys, heart, and some parts of the central nervous system such as cortex, striatum, and olfactory bulb. The high-expression level of the A3 receptor in the testis suggests a possible role for adenosine in reproduction.